2017
DOI: 10.1016/j.fuel.2017.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KCl impregnation on single particle combustion of wood and torrefied wood

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Devolatilization is an important step for both ignition and burnout of biomass particles during combustion. Several experimental studies [5][6][7][8][9] have been done to investigate biomass devolatilization under high-temperature conditions (1200℃) that are representative for pulverized biomass combustion [5,[7][8][9]. The existing studies found that the devolatilization time of biomass particles decreases with increasing gas temperature and oxygen concentration [5], and increases with increasing particle size [5][6][7][8], moisture content [7] and density [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Devolatilization is an important step for both ignition and burnout of biomass particles during combustion. Several experimental studies [5][6][7][8][9] have been done to investigate biomass devolatilization under high-temperature conditions (1200℃) that are representative for pulverized biomass combustion [5,[7][8][9]. The existing studies found that the devolatilization time of biomass particles decreases with increasing gas temperature and oxygen concentration [5], and increases with increasing particle size [5][6][7][8], moisture content [7] and density [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of the released volatiles happens relatively fast within the visual ame, while the char combustion is a more time consuming process. 1,2 Consequently, it is important to know the fractions of volatiles and char for prediction of the burnout of the fuel. The volatile and char fractions are also often used as input parameters in combustion models.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the model statistics with and without char yield data above 15 wt% daf and the original straw data can be seen in table 5. The expression for straw char yield can be seen in equation(2).The equation has not been validated against an external validation set and should thus be used more cautiously than the model for wood biomass, especially if the potassium content is vastly dierent in the sample one wants to predict the char yield of.Here CY straw is the char yield in wt%daf, KC is the potassium content in wt%db, F T is the nal temperature in K, and HR is the heating rate in K/s.…”
mentioning
confidence: 99%
“…The torrefaction process is used for thermal valorization of solid fuels, thus improving their properties, and in consequence, promoting sustainability in the energy generation sector [41][42][43]. Torrefaction is sometimes called slow pyrolysis, and it typically takes place at temperatures between 250 • C and 300 • C [44][45][46][47], with residence times ranging between 10 and 60 min [48][49][50][51]. Torrefied biomass can be an attractive fuel for the power industry for combustion and co-firing [52][53][54][55], mainly due to increased grindability [56,57], which extends the time between renovations of the mill [58], and energy density [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%